The Effect of Breathing and Skin Stimulation Techniques on Labour Pain Perception of Turkish Women - Gulay Yildirim; Nevin Hotun Sahin (Pain Research and Management)
OBJECTIVE: To determine the effect of breathing techniques and nurse-administered massage on the pain perception of pregnant woman during labour.